The transitional space of public inquiries: The case of the Australian Royal Commission into Institutional Responses to Child Sexual Abuse - Salter, Michael (The Australian and New Zealand journal of criminology, 2020)
This paper argues that the uncertain public status of victim narratives of sexual abuse has inhibited the information sharing and dialogue necessary for policy reform and transformative change. Through an integration of public sphere theory and relational psychoanalysis, the paper identifies the need for a transitional space for the explication of sexual abuse narratives in order to bridge the gap between private suffering and public understanding. The Australian Royal Commission into Institutional Responses to Child Sexual Abuse provides a case study of a transitional mechanism, with a focus on its instantiation of a therapeutic politics and the resultant synthesis of the rational-critical dimensions of public speech with the emotional depth and substance of traumatic catharsis. The paper suggests that public inquiries are uniquely positioned to act as transitional spaces between the personal and political dimensions of traumatic experience, while recognizing the challenges posed to this space by the contemporary bureaucratic state.